2021
DOI: 10.3390/nano11020355
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Photocatalytic Hydrogen Evolution over Cd1−xMnxS and CdS-β-Mn3O4-MnOOH Photocatalysts under Visible Light

Abstract: A series of solid solutions of cadmium and manganese sulfides, Cd1−xMnxS (x = 0–0.35), and composite photocatalysts, CdS-β-Mn3O4-MnOOH, were synthesized by precipitation with sodium sulfide from soluble cadmium and manganese salts with further hydrothermal treatment at 120 °C. The obtained photocatalysts were studied by the X-ray diffraction method (XRD), UV-vis diffuse reflectance spectroscopy, transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and N2 low temperature adsorption. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…For example, most The addition of earth-abundant metals has a positive effect, in particular in the case of Ni [95] and Cu [96,97]. A high activity in hydrogen evolution under visible light has been demonstrated also for solid solutions of cadmium and manganese sulfides, due to their valence and conduction band position tuning, and for composite photocatalysts, CdS-β-Mn 3 O 4 -MnOOH, due to the ternary heterojunction formation [98]. Although reasonable research progress has been accomplished on the design of photocatalysts with high-conversion efficiency, there are still some issues to be addressed.…”
Section: Photocatalytic Methodsmentioning
confidence: 99%
“…For example, most The addition of earth-abundant metals has a positive effect, in particular in the case of Ni [95] and Cu [96,97]. A high activity in hydrogen evolution under visible light has been demonstrated also for solid solutions of cadmium and manganese sulfides, due to their valence and conduction band position tuning, and for composite photocatalysts, CdS-β-Mn 3 O 4 -MnOOH, due to the ternary heterojunction formation [98]. Although reasonable research progress has been accomplished on the design of photocatalysts with high-conversion efficiency, there are still some issues to be addressed.…”
Section: Photocatalytic Methodsmentioning
confidence: 99%
“…Cadmium–zinc sulfides are the widely studied photocatalysts [ 8 ]. As for cadmium–manganese sulfides, it was recently shown that they also exhibit high photocatalytic activity [ 9 , 10 , 11 , 12 , 13 ]. Unlike zinc cations, Mn 2+ cations can be easily oxidized by photogenerated holes to the oxidation state of 3+; thus, the mechanism of the action of (Cd,Zn)S and (Cd,Mn)S photocatalysts may differ.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we analyzed the structure and morphology of Cd 1−x Mn x S (x~0.3) nanoparticles in composite photocatalysts, which are active during the decomposition of water to produce hydrogen [ 12 , 13 ]. The investigation was made by X-ray diffraction via the Debye Function Analysis.…”
Section: Introductionmentioning
confidence: 99%